Salt marshes of the Cape (South Africa) : vegetation dynamics and interactions - O'Callaghan, M.(Michael G.) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1993.